2015
DOI: 10.1146/annurev-publhealth-031914-122444
|View full text |Cite
|
Sign up to set email alerts
|

Focused Deterrence and the Prevention of Violent Gun Injuries: Practice, Theoretical Principles, and Scientific Evidence

Abstract: Focused deterrence strategies are a relatively new addition to a growing portfolio of evidence-based violent gun injury prevention practices available to policy makers and practitioners. These strategies seek to change offender behavior by understanding the underlying violence-producing dynamics and conditions that sustain recurring violent gun injury problems and by implementing a blended strategy of law enforcement, community mobilization, and social service actions. Consistent with documented public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 50 publications
2
24
0
1
Order By: Relevance
“…Moreover, evidence suggests that crime prevention can be achieved without resorting to an unrestricted SQF policy. A generation of studies has now shown that when police focus efforts on high-crime places or people, they can achieve crime-prevention gains (Braga and Weisburd, 2015;Kennedy, 1996;Sherman, 2007). In particular, consistent experimental evidence shows that police focusing on hot spots of crime will yield crime reductions (Braga et al, 2014;Sherman and Weisburd, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence suggests that crime prevention can be achieved without resorting to an unrestricted SQF policy. A generation of studies has now shown that when police focus efforts on high-crime places or people, they can achieve crime-prevention gains (Braga and Weisburd, 2015;Kennedy, 1996;Sherman, 2007). In particular, consistent experimental evidence shows that police focusing on hot spots of crime will yield crime reductions (Braga et al, 2014;Sherman and Weisburd, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in an investigation of the life-course factors that influence gun carrying among young urban males, Lizotte, Krohn, Howell, Tobin, and Howard (2000) found that membership in a gang was a major factor for handgun carrying during early adolescence, while drug dealing, drug use, and peers effects had stronger effect among older adolescents. Therefore, focused deterrence (Braga & Weisburd, 2015) around gang-involved youth and adolescent drug abuse may prove useful. Boston's Operation Ceasefire program observed a significant reduction in gun violence by holding all members of a gang culpable if one member used a handgun illegally (Braga & Pierce, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews of parent training interventions have identified similar beneficial effects (e.g., Piquero, Farrington, Welsh, Tremblay, & Jennings, 2009 Although handgun carrying is embedded into a net of externalizing behavior liability, research has begun to establish that there are more direct interventions that can reduce gun violence. For example, key high-risk individuals, usually gang members, are told directly that they are under intense scrutiny and will be held accountable though a variety of sanctions for which they are vulnerable to such as conditions of probation and parole or ongoing investigations involving members of the gang (Braga & Weisburd, 2015). The theoretical mechanism behind the effectiveness of these approaches is focused deterrence (Braga, 2012;Braga & Weisburd, 2015).…”
Section: Policy and Preventionmentioning
confidence: 99%